KONSENTRASI DAN KUALITAS PERGURUAN TINGGI SWASTA (SUATU STUDI PADA LLDIKTI WILAYAH XIV PAPUA DAN PAPUA BARAT) - Metha Gomies (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2019)
In an effort to improve the nation's competitiveness through tertiary institutions in EasternIndonesia (KTI), this study aims to find out how far the concentration of Private Universities(PTS) and the quality of PTS in Regional XIV, Papua, and West Papua LLDIKTI, by using: (1 )Simple statistical analysis tools, to identify the location of the education service industry and inwhich areas they tend to group spatially; and (2) Table Analysis, to see the quality of PTS.Found: the first model, Geographically it appears that at the provincial level there were 41private universities or 68.33 percent of the 60 private universities concentrated in PapuaProvince, and in West Papua Province which was 31.67 percent. While at the district / city level,it describes that those included in the high concentration group are in all cities in each provincein the Region XIV LLDIKTI in high classification (City: Jayapura, and Sorong), has around 22PTS or 36.67% of the total PTS. While the included in the middle classification with the numberof PTS as many as 35 PTS or 58.33% (Regency: Jayapura, Biak Numfor, Mimika, Merauke,Jayawijaya, Sorong, Manokwari, and Fakfak), and those included in the low classification are asmany as PTS 3 PTS or 5.00% (Regency: Nabire, Yapen Waropen, and Bintuni); in the secondmodel, the quality of PTS seen according to the Institutional Accreditation status shows thatthere are only 23 private universities or around 38.33% in the area of LLDIKTI Wilayah XIV,which is accredited. Study Program Accreditation shows that out of 238 study programs, whichhave been accredited by BAN-PT as many as 215 or around 90.34% of study programs thathave been accredited. However, most of the study programs are still accredited C, which is 149study programs or around 69.30%. While the remaining is B cited as many as 66 studyprograms or 30.70%.It is suggested: (1) the government needs attention in overcoming the concentration levelof PTS which tends to be in the city center, both through improving the quality of humanresources (HR) and regional economic development; (2) government attention is needed inpreparing human resources in each region that can be a leader for efforts to improve the qualityof PTS in meeting the expectations of the Ministry of Research and Technology; (3) anexpanded institutional capacity building program is needed.